Comparative analysis of primary tumour and matched metastases in colorectal cancer patients: Evaluation of concordance between genomic and transcriptional profiles. Issue 7 (May 2015) - Vignot, Stéphane; Lefebvre, Céline; Frampton, Garrett M.; Meurice, Guillaume; Yelensky, Roman; Palmer, Gary; Capron, Frédérique; Lazar, Vladimir; Hannoun, Laurent; Miller, Vincent A.; André, Fabrice; Stephens, Philip J.; et al.
Highlights Intratumoural heterogeneity represents a major challenge for precision medicine. Molecular variability was investigated in 13 metastatic colorectal cancer patients. Mutational and gene expression (GE) analysis were performed. Profile of primary tumour can identify key somatic alterations in matched metastases. GE identified specific pathways associated in metastatic progression.